Résilience et discussion à visée philosophique en lycée professionnel : en quoi la DVP s’inscrit comme médiation facilitant un processus de résilience à l’école - Johanna Henrion (Éducation et Socialisation)
This article explains the necessity of the mediation supported by the discussion with philosophic aim in the field of the theories of the impact strength at the school, and particularly in professional high school, with teenagers stemming from the priority and specialized education. Locked into the academic and social failure, the carriers of problems of behavior between mistrust and stupor, they refuse the proposal of the adult which confronts them with the knowledge to drive them to think by themselves, exactly on their thoughts deviants or maladjusted persons. The practice of the mediation by the discussion with philosophic aim around existential concepts seems a support towards a possible of reversible thoughts. Through the verbal and cognitive work mediatized by the DVP according to four big families of skills at the teenager, it would be possible to give meaning to the previous experiments, to invest the future, the schooling, and allow a thought and adapted resumption of development, in the philosophy of the school impact strength.